Comprehensive preliminary analysis of innovation and investment projects in housing construction - Tytok, V. (Ways to Improve Construction Efficiency, 2015)
In this article are proposed the methodological and methodical principles and regulations of complex character for project analysis. These principles and regulations were worked out in relation to innovation investment projects in residential construction.